Experimental Research on Determining the Transmittance of Lenses for Vision Correction and the Factors that Influence It - Beatrice Daniela TUDOR; Iustina BĂBUȘANU (The Annals of “Dunarea de Jos” University of Galati. Fascicle IX, Metallurgy and Materials Science)
The field of making optical lenses is very vast and with great applicability in several engineering fields. The research carried out in this work implied the determination of the transmittance of optical lenses of different diopters, thicknesses, with and without protection and the influence of material from which they were made. By analysing different aspects of lenses, we can better understand their impact on patients' vision and visual comfort, thus contributing to improving the quality of ophthalmic services.